The effects of lyrical fit in advertisements - Joanne, P. S. Yeoh (Associated Management Consultants, 2021)
Music’s ability to suggest certain brand impressions were investigated in this study based on the theory of ‘musical fit.’ This is because music/voice content that ‘fit’ should prime certain impressions of the listeners’ knowledge for the brand and an increase/decrease in liking for the advertised product. This study, in particular, investigated the effects of using popular music with lyrics that ‘fitted’ an advertised product. Participants watched one of three versions of an advertisement whereby lyrics were varied in each version. The music selections were similar in lyrical meaning, tempo, style, rhythm, etc. The results contradicted previous findings; implying that music with lyrics that ‘fit’ may not necessarily improve affective responses to brand impressions. The implications of this were discussed in terms of Berlyne’s theory and the limitations of musical fit.